Preparing for the Future of Education: Adapting to the Technological Revolution and the World of Work - Karim Noura (FOUNDAE (Foundation of Advanced Education), 2024)
The rapid advancement of modern technology, particularly automation and digital communication, has transformed various industries, including education and employment. As automated tools and robotics replace human workers in several sectors, the demand for a highly skilled workforce continues to grow. However, there remains a critical gap in the preparedness of young professionals for future job markets. This study aims to analyze the evolving educational and workforce landscape by examining industry trends and the role of key stakeholders in shaping educational policies. Using a qualitative approach, this research gathers insights from experienced educators and industry professionals to identify essential skills and competencies required in the digital era. The findings highlight the urgent need for adaptive and interdisciplinary education models that bridge the gap between traditional curricula and industry demands. This study underscores the importance of collaboration between educational institutions, policymakers, and industry leaders to foster a future-ready workforce